2016
DOI: 10.3390/computation4030031
|View full text |Cite
|
Sign up to set email alerts
|

Computational Analysis of Natural Ventilation Flows in Geodesic Dome Building in Hot Climates

Abstract: For centuries, dome roofs were used in traditional houses in hot regions such as the Middle East and Mediterranean basin due to its thermal advantages, structural benefits and availability of construction materials. This article presents the computational modelling of the wind-and buoyancy-induced ventilation in a geodesic dome building in a hot climate. The airflow and temperature distributions and ventilation flow rates were predicted using Computational Fluid Dynamics (CFD). The three-dimensional Reynolds-A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 27 publications
1
23
0
Order By: Relevance
“…In certain cases, they found that wind flow direction and speed are not essential in decreasing room temperature of the domed roofs. Soleimani et al (2016) conducted a computational simulation of the wind-induced ventilation in a geodesic dome in a hot climate. They reported that natural ventilation by upper roof openings can reduce the indoor air temperature during winter periods.…”
Section: Review Of Vaulted and Domed Roofsmentioning
confidence: 99%
“…In certain cases, they found that wind flow direction and speed are not essential in decreasing room temperature of the domed roofs. Soleimani et al (2016) conducted a computational simulation of the wind-induced ventilation in a geodesic dome in a hot climate. They reported that natural ventilation by upper roof openings can reduce the indoor air temperature during winter periods.…”
Section: Review Of Vaulted and Domed Roofsmentioning
confidence: 99%
“…Reasonable air distribution is a necessary guarantee for effective ventilation (Etheridge 2011). The uniformity of indoor airflow field can reduce internal vortices and improve ventilation performance (Soleimani et al 2016). On the other hand, evaluation indicators of effective ventilation for the LSCCSD, with the particular annular opening, should be specially considered.…”
Section: Introductionmentioning
confidence: 99%
“…The wind tunnel validation of Norton et al (2009) is based on the same 1/2 scale model parameters as the wind tunnel test, and then extended to full-scale CFD for calculation and simulation. For dome building, Soleimani et al (2016) carried out CFD validation by the wind tunnel test of Rahmatmand et al (2014) on the external flow field, and further extended to study internal and external flow field. The calculation results of Evola and Popov (2006) showed that the ventilation deviation between CFD and wind tunnel test is reasonable, and the internal air distribution is well demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…The building sector is one of the most energy consuming sectors, and it is responsible for about the 30%-40% of the world's total energy consumption. The utilization of alternative and renewable energy sources in the building sector is a critical issue which has to be delivered in order to achieve sustainability [1]. Solar energy exploitation is an important weapon for reducing electricity and fossil fuel utilization in the building sector [2].…”
Section: Introductionmentioning
confidence: 99%